Profil Paramater Inflamasi Albumin Dan Prokalsitonin Pada Kasus Pasien Covid-19 - Octifani, Amellya; Rahman, Nur Aisyah (Lembaga Publikasi Ilmiah Nusantara, 2023)
Patients with COVID-19 have increased serum levels of Procalcitonin and decreased albumin, a key inflammatory marker associated with a high risk of organ injury and death. This study aims to determine the profile of inflammatory parameters albumin and procalcitonin in covid-19 patient cases. The type of research used is retrospective with a cross sectional approach. The research data were taken using a simple random sampling technique. Analysis for albumin with severity in COVID-19 positive patients in this study used an optimal limit or cut-off value of 3.5 g/dL. The optimal limit or cut off value for Procalcitonin in this study was 0.05 µg/L. The results of research from 30 patient data showed that there was a decrease in albumin levels in moderate and severe patients by 60% and an increase in procalcitonin levels > 0.05 µg/L by 96%. The conclusion of this study is that there was a decrease in albumin levels and an increase in procalcitonin levels in COVID-19 case patients, which indicates inflammation due to SARS-COV2 virus infection.